Osteoking Decelerates Cartilage Degeneration in DMM-Induced Osteoarthritic Mice Model Through TGF-β/smad-dependent Manner - Ling, Houfu; Zeng, Qinghe; Ge, Qinwen; Chen, Jiali; Yuan, Wenhua; Xu, Rui; Shi, Zhenyu; Xia, Hanting; Hu, Songfeng; Jin, Hongting; Wang, Pinger; Tong, Peijian (Frontiers in Pharmacology, 2021)
Osteoarthritis (OA) is a common disease characterized by cartilage degeneration. In current, much attentions have been attracted on Traditional Chinese Medicine (TCM) since its efficacy of ameliorating cartilage degradation with mild side effects. Osteoking, a TCM prescription, has long been used in OA treatment. However, the exact mechanism of Osteoking is not fully elucidated. In current study, destabilization of the medial meniscus (DMM)-induced OA mice were introduced as wild type animal model. After 8 weeks of administration of Osteoking, histomorphometry, OARSI scoring, gait analysis, micro-CT and immunohistochemistry for Col2, MMP-13 and pSmad-2 were conducted to evaluate the chondroprotective effects of Osteoking. Furthermore, TGFβRIICol2ER transgenic mice were constructed and introduced in current study to validate whether Osteoking exerts its anti-OA effects via TGF-β signaling pathway. Results demonstrated that in wild type DMM-induced OA mice, Osteoking ameliorated OA-phenotype including cartilage degradation, subchondral bone sclerosis and gait abnormality. Also, Col2 and pSmad-2 expressions were found to be up-regulated after Osteoking treatment, while MMP-13 was down-regulated. In TGFβRIICol2ER mice, spontaneous OA phenotype was found and treatment of Osteoking failed to reverse the OA spontaneous progression, suggested that the Osteoking ameliorates OA progression via TGF-β signaling pathway. In conclusion, Osteoking ameliorates OA progression by protecting cartilage degradation and alleviating subchondral bone sclerosis via TGF-β signaling pathway.